(3GdeLdS GdChd ef CeGdi TeS GdOjf eMeO Hf YHO Gddg CHj HcQ Hf eMeO GdbjSi GdTgjQ HGHf fGUQ GdOjfs - (3TeS GdOjf eMeO Hf YHO Gddg Hf eMeO GdbjSi GdOeTbj GdeYQha HGHf fGUQ GdOjf,J (B842 (3g` s ((3fLe GdOjf YeQ Hf eMeO s)
(3ChdgG (B:s
(3MOKfG TjNfG TjN GdGSdGe SQGL GdOjf CHh MaU YeQ Hf fUjQ ef daXg hMaXg HLGeY OeTb s
(3BNQgG (B:s
(3cPG Ydi Bdg hGdUMH CLeYge hGdJGHYjf dge YbOkG Ch EjeGfkG BNQ GdeLdS GdChd ef CeGdi SjOfG TeS GdOjf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW eged GdfbWs
(3cJHJ HEedGA GdeDda Ydi GdfGSN Ydi MGTjI fSNJfG gPg hHBNQgG SeGYGJ ef fGSNgG hBNQjf YdeGA Ydi GdeDda efgG (B836 (3SfI (B837 (3hTgO GdeDda Ydi gPg GdSeGYGJ hCLGRgG HNWg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs